Development of the PEACH Model to Improve Toilet Training Skills in Autistic Children at SLB - Zahrotin Nisa; Fajar Wahyu Prasetyo; Ratna Wulandari (Universitas Palangka Raya, 2026)
Toilet training is a fundamental adaptive skill that supports independence in autistic children. However, its implementation in special education settings is often hindered by limited visual media, functional guidance, and structured assistance procedures. This study aimed to develop and examine the feasibility and preliminary effectiveness of the PEACH model, which integrates the Picture Exchange Communication System (PECS), Affective Communication Training (AFFACT), and Treatment and Education of Autistic and Related Communication-Handicapped Children (TEACCH), to improve toilet training skills among autistic elementary school students at SLB Negeri Banyuwangi. This study employed a 4D research and development design involving needs analysis, product design, expert validation, limited trials, and field testing. Three autistic students participated in a one-group pretest-posttest field test. Data were collected using validation sheets, observation checklists, interviews, and documentation. The feasibility scores for the PEACH material, media, and practitioner assessments were 85.50%, 94.00%, and 92.50%, respectively, indicating that the product was highly feasible. The mean toilet training score increased from 22.67 to 38.67, with an N-Gain score of 0.63 in the moderate category and a significant paired-sample t-test result (p = 0.001). These findings indicate that the PEACH model is feasible and preliminarily effective in supporting toilet training independence among autistic children.